Litteraturfaglig praksis: Avgangselevers retrospektive blikk på arbeid med litterære tekster i videregående skole - Aslaug Fodstad Gourvennec (Nordic Journal of Literacy Research, 2016)
The discussion and revision of the Norwegian school’s role and mission for the future (NOU 2015:8) draws attention to the ever ongoing negotiation between tradition and trends in the disciplines. This article seeks to contribute to knowledge on central aspects of literature education within the subject of Norwegian in upper secondary school, by studying how matriculating students describe this practice. In two group interviews, these students recontextualise, retrospectively, the literary practice which they have encountered in school and their own development within the frames of this practice. The article investigates how the students describe the participants, actions and resources of the practice, and the core values that structure their descriptions of the practice. The study indicate that the students experience a tension between the different frames in teaching practice, that lead towards or away from the subject core, and that students behave differently when experiencing this tension. Despite variations in preferences and behaviour, the students are in accord in describing how a combination of work with challenging literate texts over time and with different ways of working, lead to situations characterised by deep understanding, multiple interpretations, critical thinking and participation – all aspects in line with their conception of the disciplinary core. The article argues for the necessity of considering the students as participants in the literary community of practice.